Bâkî’nin Gazellerine Ek ve Derzi-zâde ‘Ulvî’ye Nazîreleri - (:unkn) unknown (My University, 2017)
Osmanlı edebiyatı şairlerinin çeşitli sebeplerle divanlarına dahil etmedikleri yahut divanlarını tertip ettikten sonra that they did not include in their divans for various reasons yazdıkları şiirler vardır. Bu şiirlere yine bu sahanın mahsulor they wrote after arranging their divans. These poems lerinden olan mecmualarda veya başka eserlerin içerisinde can be also coincied with in the majmuas or another litedenk gelinebilmektedir. Mecmuaların yanı sıra az da olsa rary works of this field crops. In addition to the majmuas, bazı divan nüshalarında başka şairlerin şahıs ve eserlerine in a small number of diwan copies contain new informayönelik yeni bilgilere rastlanır. Bu şekilde ortaya çıkan her tion about personality and works of another poets are bilgi, öncesinde yapılan çalışmaların eksiklerini tamamla-encountered. Any information that emerges in this way yarak kapsamını genişletmektedir. broadens the scope by complementing the shortcomings of Bâkî (ö. 1600) de bu türden örneğine sıkça rastlanılan şairlerden biridir. Bu sebeple mecmualardan hareketle Osmanlı edebiyatının en müstesna şair ve devlet adamlarından tered in this kind of example. For this reason, studies have biri olan Bâkî'nin divanında yer almayan gazellerine been carried out on the ghazals of Bâkî, one of the most yönelik çalışmalar yapılagelmiştir. Bu makalede ise Derzi-exceptional poets of Ottoman literature and a statesmen, zâde 'Ulvî (ö. 1585)'nin divan yazmalarından birinin which are not included in the divan. In this article, the derkenarında karşılaşılan ve Bâkî'nin önceki yayınlarda poems of Baki, which are encountered in the edge of one of bulunmayan şiirlerine yer verilecektir. Ayrıca aynı yazthe copies of the Derzi-zade 'Ulvî (d. 1585)'s Divan, which madan hareketle Bâkî'nin şimdiye kadar herhangi bir vesile are not found in the previous publications, will be given. ile değinilmeyen çağdaşı Derzi-zâde 'Ulvî'nin gazelleri In addition, through the same manuscript, Bâkî's naziras zemininde yazdığı nazireleri tanıtılacaktır. Burada Bâkî'ninto his coeval Derzi-zâde 'Ulvî's ghazals will be introduced, Dîvân'ında bulunmayan gazelleri kadar nazireleri de 'Ulvî which have not been mentioned on any study. Here it is ile etkileşimini gözler önüne sermesi ve şiirleri kıyaslan-very important that the naziras as well as the ghazals that dığında 'Ulvî'nin de en az Bâkî kadar kudretli bir şair olduare not in the Divan of Bâkî show that 'Ulvî is at least as ğunu göstermesi bakımından oldukça önemlidir

There are poems written by Ottoman Literature poets that they did not include in their divans for various reasons or they wrote after arranging their divans. These poems can be also coincied with in the majmuas or another literary works of this field crops. In addition to the majmuas, in a small number of diwan copies contain new information about personality and works of another poets are encountered. Any information that emerges in this way broadens the scope by complementing the shortcomings of previous studies. Bâkî (d. 1600) is also one of the poets frequently encountered in this kind of example. For this reason, studies have been carried out on the ghazals of Bâkî, one of the most exceptional poets of Ottoman literature and a statesmen, which are not included in the divan. In this article, the poems of Baki, which are encountered in the edge of one of the copies of the Derzi-zade ‘Ulvî (d. 1585)'s Divan, which are not found in the previous publications, will be given. In addition, through the same manuscript, Bâkî’s naziras to his coeval Derzi-zâde 'Ulvî’s ghazals will be introduced, which have not been mentioned on any study. Here it is very important that the naziras as well as the ghazals that are not in the Divan of Bâkî show that 'Ulvî is at least as mighty as the Bâkî when his poetry is compared to his.
The Addition to Baki's Ghazals and His Naziras to Derzi-zâde Ulvi
Keywords: Edebiyat